2014
DOI: 10.1111/jnc.12937
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the peripheral sink hypothesis: inhibiting BACE1 activity in the periphery does not alter β‐amyloid levels in the CNS

Abstract: Aggregation of amyloid beta (Ab) peptides and the subsequent neural plaque formation is a central aspect of Alzheimer's disease. Various strategies to reduce Ab load in the brain are therefore intensely pursued. It has been hypothesized that reducing Ab peptides in the periphery, that is in organs outside the brain, would be a way to diminish Ab levels and plaque load in the brain. In this report, we put this peripheral sink hypothesis to test by investigating how selective inhibition of Ab production in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 31 publications
6
20
0
1
Order By: Relevance
“…This suggests that in rodents, endogenous BACE1 levels are well above the levels necessary for APP processing. These findings demonstrate that the biochemical consequences of BACE1 deletion, at least with respect to APP processing, are consistent between rats and mice42434445 and in alignment with observations in humans following treatment with BACE1 inhibitors46474849, suggesting that this rat model has adequate predictive validity as a translational model in these measures.…”
Section: Discussionsupporting
confidence: 79%
“…This suggests that in rodents, endogenous BACE1 levels are well above the levels necessary for APP processing. These findings demonstrate that the biochemical consequences of BACE1 deletion, at least with respect to APP processing, are consistent between rats and mice42434445 and in alignment with observations in humans following treatment with BACE1 inhibitors46474849, suggesting that this rat model has adequate predictive validity as a translational model in these measures.…”
Section: Discussionsupporting
confidence: 79%
“…For example, it has been suggested that cerebral Ab accumulation may be partly a downstream consequence of age or vascular diseaseerelated microvascular injury (Sagare et al, 2013). Alternative theories have also been substantiated by studies demonstrating differential impact of anti-Ab antibodies on Ab levels in the blood and peripheral blood suggesting that soluble AB may need to be depleted within the central nervous system instead of the peripheral blood system (Georgievska et al, 2014;Henderson et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Methods of voxel-based morphometry used to estimate brain tissue volumes have been previously described (Godin et al, 2009;Lemaitre et al, 2005b). Images were sent to the database repository.…”
Section: Image Analysismentioning
confidence: 99%
“…This peripheral sink hypothesis is based on the influx–efflux transport across the brain vessel walls into the blood stream. It was shown in recent work that continued inhibition of peripheral BACE1 affects the brain levels of Aβ much less than the peripheral levels [59]. In addition, degrading Aβ only peripherally with neprilysin does not affect the central levels of Aβ [60].…”
Section: Discussionmentioning
confidence: 99%